2022
DOI: 10.1088/2515-7620/aca5f2
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric precursors to the Antarctic sea ice record low in February 2022

Abstract: Antarctic sea ice expansion and recession are asymmetric in nature, with regional and temporal variations. The decade-long overall increase in the Antarctic sea ice extent (SIE) until 2015 showed a decrease in recent years since satellite records were available. The present study focused on determining the atmospheric forcing and climate fluctuations responsible for the lowest SIE record in February 2022. Here, the lowest SIE record was assumed to result from the sea ice recession that began in September 2021.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…Individual extreme sea ice events have been linked to anomalous atmospheric circulation events. For example, the strong meridional circulation associated with zonal wave number three contributed to the low sea ice in spring 2016 17 , while a strong Amundsen Sea Low circulation in spring 2021 influenced the low spring/summer sea ice conditions in 2021/22 18,19 . However, the phase of the Southern Annular Mode cannot account for the low Antarctic sea ice over recent years: the positive phase of the Southern Annular Mode has historically been associated with colder sea surface temperatures and increased sea ice extent 7 , and in line with this, the 2017 record summer sea ice minimum (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Individual extreme sea ice events have been linked to anomalous atmospheric circulation events. For example, the strong meridional circulation associated with zonal wave number three contributed to the low sea ice in spring 2016 17 , while a strong Amundsen Sea Low circulation in spring 2021 influenced the low spring/summer sea ice conditions in 2021/22 18,19 . However, the phase of the Southern Annular Mode cannot account for the low Antarctic sea ice over recent years: the positive phase of the Southern Annular Mode has historically been associated with colder sea surface temperatures and increased sea ice extent 7 , and in line with this, the 2017 record summer sea ice minimum (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Holland et al, 2017;, and previous works examining the 2017 and 2022 minima also considered this season (e.g. Purich and England 2019;Yadav et al 2022). Furthermore, as seen in the previous section, the sea ice anomalous conditions are already set up in January at the latest, indicating the important role of surface winds during the previous months.…”
Section: Atmospheric Circulation and Surface Windsmentioning
confidence: 62%
“…More recently, Yadav et al (2022) specifically focused on the atmospheric precursors of this event during the preceding months, i.e. since September 2021.…”
Section: Introductionmentioning
confidence: 99%
“…Sea-ice extent remained close to record low levels during most of the summer 2021-22. Yadav et al [62] showed that the sea ice deficit around the AP was linked to persistent warm northerly flow in the Amundsen/Bellingshausen sector throughout the summer 2021/2022 (from November 2021 until February 2022) linked to the anomalously deep Amundsen Sea Low, while sea ice anomalies in the northern Weddell Sea were to a large extent caused by stronger westerlies associated with positive SAM during the entire summer season. Wang et al [61] emphasized that the Amundsen Sea sea ice loss was more dynamically related, while a strong surface melt contributed to the Weddell Sea sea ice minimum.…”
Section: Comparison With Recent Ap Heatwavesmentioning
confidence: 99%